"Synthesis and Identification of (4, 5, 6 and 7) Membered Heterocyclic Derivatives from 5-nitrovanilline” - Shaimaa Adnan Behget (Journal of Global Pharma Technology, 2018)
AbstractThis work included synthesis new Schiff base (1-(3-((4-hydroxy-3-methoxy-5 nitrobenzylidene) amino) phenyl) ethan-1-one)(1)by reaction 5-nitrovanilline with3-aminoacetophenone in acid medium, then (1) react with 2-amino-6-methoxybenzothazole to get derivative(2). (2) React with (chloroacetylchloride, thioglycolic acid, glycine, alanine, sodium azide, phthalic anhydride, maleic anhydride) to give (β-lactam, thiazolidine, imidazolidine, tetrazole, oxazepine) derivatives. In other side5-nitrovanilline react with acetophenone derivative in alkaline medium to get3-(4-hydroxy-3-methoxy-5-nitrophenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one which react with (hydrazine , phenyl hydrazine , 2,4-dinitro phenyl hydrazine , hydroxyl amine hydrochloride , urea , thiourea , ethyl cyanoacetate , malononitrile , guanidine hydrochloride ) to get ( pyrazol , isoxazole , oxazine , thiazine ,  pyridine , pyrimidine ) derivatives. The new synthesized compounds have been identified by their melting points, 1HNMR, 13CNMR and FT-IR spectra.Keywords: Schiff bases, Chalchone,β-lactam, Thiazolidine, imidazolidine, Tetrazole, oxazepine, Pyrazol, Isoxazole , Oxazine , Thiazine ,  Pyridine , Pyrimidine.